Pasai and Constantinople: Hybrid Legitimacies and Multiple Identities in the 15th Century Muslim Societies - Baiquni Hasbi; Rasyidin Muhammad (Al-Jami'ah Research Centre, 2025)
This article provides an alternative historical explanation that challenges the monolithic portrayal of premodern Muslim polities. Prevailing narratives often emphasize Islam as the sole dominant identity, relegating Southeast Asia to the ‘periphery’ of the Islamic world and reducing the Ottoman governance to purely Islamic ideals. This article reconsiders how Muslim polities in the fifteenth century forged legitimacy through strategies that were neither monolithic nor exclusively Islamic. Focusing on the Sultanate of Pasai in Sumatra and the Ottoman Empire in Constantinople, it demonstrates how rulers embedded themselves in multiple traditions, Islamic, Indic, indigenous, and Greco-Roman Christian, at once. Through textual analysis of primary texts, Hikayat Raja-Raja Pasai, Tarih-i Ebü’l Fath, Târih-i Beyân-ı Binâ-yı Ayasofya-yı Kebîr, and History of Mehmed the Conqueror, this study demonstrates that both Pasai and the Ottomans integrated hybrid traditions to construct their sovereignty. Highlighting these multilayered repertoires adopts a polycentric rather than center-periphery framework, one in which Southeast Asia and the Mediterranean emerge as dynamic, interconnected sites of Muslim statecraft.[Artikel ini menawarkan sebuah penjelasan historis alternatif yang ingin menantang gambaran monolitik tentang kerajaan muslim pramodern. Narasi yang dominan selama ini masih cenderung menekankan Islam sebagai identitas tunggal yang mendominasi, sehingga menempatkan Asia Tenggara sebagai “pinggiran dunia Islam” dan mereduksi identitas Kekaisaran Utsmani hanya menjadi sekadar Islam semata. Artikel ini meninjau kembali bagaimana Kerajaan Muslim pada abad kelima belas membangun legitimasi melalui strategi yang tidak bersifat monolitik maupun eksklusif Islami. Dengan studi kasus Kesultanan Pasai di Sumatra dan Kekaisaran Utsmani di Konstantinopel, artikel ini menunjukkan bagaimana para penguasa menggabungkan berbagai tradisi sekaligus, Islam, lokal, Indic, dan Greko-Romawi Kristen. Melalui analisis beberapa teks primer seperti Hikayat Raja-Raja Pasai, Tarih-i Ebü’l Fath, Târih-i Beyân-ı Binâ-yı Ayasofya-yı Kebîr, dan History of Mehmed the Conqueror, kajian ini memperlihatkan bahwa baik Pasai maupun Usmani mengintegrasikan tradisi-tradisi hibrida untuk membangun legitimasi dan kedaulatannya. Untuk menjelaskan khazanah yang berlapis ini, artikel ini mengadopsi kerangka polisentris dari pada model pusat-pinggiran, di mana Asia Tenggara dan Mediterania muncul sebagai pusat-pusat dinamis yang saling saling terhubung dalam praktik Kerajaan Muslim.]